Correction to: Ni Flower/MXene-Melamine Foam Derived 3D Magnetic/Conductive Networks for Ultra-Efficient Microwave Absorption and Infrared Stealth - Cheng, Haoran; Pan, Yamin; Wang, Xin; Liu, Chuntai; Shen, Changyu; Schubert, Dirk W.; Guo, Zhanhu; Liu, Xianhu (Nano-Micro Letters, 2022)
The development of multifunctional and efficient electromagnetic wave absorbing materials is a challenging research hotspot. Here, the magnetized Ni flower/MXene hybrids are successfully assembled on the surface of melamine foam (MF) through electrostatic self-assembly and dip-coating adsorption process, realizing the integration of microwave absorption, infrared stealth, and flame retardant. Remarkably, the Ni/MXene-MF achieves a minimum reflection loss (RLmin) of − 62.7 dB with a corresponding effective absorption bandwidth (EAB) of 6.24 GHz at 2 mm and an EAB of 6.88 GHz at 1.8 mm. Strong electromagnetic wave absorption is attributed to the three-dimensional magnetic/conductive networks, which provided excellent impedance matching, dielectric loss, magnetic loss, interface polarization, and multiple attenuations. In addition, the Ni/MXene-MF endows low density, excellent heat insulation, infrared stealth, and flame-retardant functions. This work provided a new development strategy for the design of multifunctional and efficient electromagnetic wave absorbing materials. Highlights: 1 Ni-MXene/MF foam is synthesized via an electrostatic assembly and dip-coating process. 2 The “micro-capacitor” structure of Ni/MXene and the 3D porous structure of MF endow the foam excellent impedance matching and wave absorption performance. 3 The excellent heat insulation, infrared stealth, and flame-retardant performances are achieved.